Clinical effect of scraping therapy in the treatment of knee osteoarthritis - Jin-Rong WEI; Hui-Ping ZHANG; Shu-Ying XU; M A Bo; Jin-Hua ZHANG; Jia LIU (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this study is to investigate the effect of scraping therapy in the treatment of knee osteoarthritis. Materials and Methods: A total of eighty patients with knee osteoarthritis were assigned to the moxibustion group and the scraping therapy group according to the random numerical table method, with forty cases in each group. Patients in both two groups received functional exercise and moxibustion therapy, and those in the scraping therapy group were supplemented with scraping therapy. The serum indexes of interleukin-1 (IL-1), IL-6, tumor necrosis factor-alpha (TNF-α), and superoxide dismutase (SOD) were detected before and after the treatment. The clinical syndrome integral and Visual Analog Scale (VAS) on pain of patients were assessed. The clinical therapeutic efficacy was evaluated and compared between the two groups. Results: Patients in the scraping therapy group received better outcomes of serum IL-1, IL-6, TNF-α, and SOD compared with those in the moxibustion group at 2 months after treatment (P < 0.05). The scores of clinical syndrome integral and VAS on pain were decreased in two groups at 2 months after the treatment and were lower in the scraping therapy group than those in the moxibustion group (P < 0.05). The overall effective rate in the scraping therapy group was higher than that in the control group (87.50% vs. 67.50%, P < 0.05). Conclusion: The scraping therapy is potentially effective to ameliorate the clinical symptom and pain degree of patients with knee osteoarthritis.